VALENTYN SILVESTROV’S STRING QUARTETS WITHIN THE DYNAMICS OF GENRE TRADITION: FROM MODERNISM TO METAMUSIC - VARAKUTA, Maryna; KUPINA, Daryna; VOTINTSEVA, Maryna (Studia Universitatis Babes-Bolyai Musica, 2025)
The article is devoted to studying the manifestation of the genre tradition of the string quartet in the music of Valentyn Silvestrov, tracing its diachronic dynamics from modernism to “metamusic”. Genre tradition is defined as a system that combines invariants (monotimbral ensemble, the one-player–one-part principle, quartettistic symphonism, dialogic chamber rhetoric) with variable peripheries (textural and timbral techniques, intertextual codes, articulation–metric profiles), through which the “memory of the genre” is preserved and renewed. The article examines Quartetto piccolo (1961), String Quartet No. 1 (1974), No. 2 (1988), and No. 3 (2011). On the basis of comparative analysis, it is demonstrating that: in the early period serial/ sonoristic procedures are counterbalanced by lyric cantabile; the post-avant-garde phase articulates a dialogue between the romantic code and contemporary sound masses/cluster textures; the postludial poetics of silence and resonance acquires a form-bearing function; intercultural topoi (notably Irish modal–pastoral formulae in No. 3) are integrated within the quartet matrix without eroding identity. It is argued that Silvestrov’s quartets operate as meta-texts of the European chamber tradition. The study proposes a typology of indicators (form, texture, intonation, dynamic relief, timbral technique, articulation/metric patterns, reception), offering a replicable protocol for further analyses and refining the understanding of how the quartet functions today as an actual model of musical memory.